2000
DOI: 10.1200/jco.2000.18.22.3748
|View full text |Cite|
|
Sign up to set email alerts
|

Anastrozole Versus Tamoxifen as First-Line Therapy for Advanced Breast Cancer in 668 Postmenopausal Women: Results of the Tamoxifen or Arimidex Randomized Group Efficacy and Tolerability Study

Abstract: Anastrozole satisfied the predefined criteria for equivalence to tamoxifen. Together with the lower observed incidence of thromboembolic events and vaginal bleeding, these findings indicate that anastrozole should be considered as first-line therapy for postmenopausal women with ABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
361
0
21

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 775 publications
(394 citation statements)
references
References 27 publications
10
361
0
21
Order By: Relevance
“…However, in most studies the investigators actually intended to identify those kRT-PCR mRNA cutoff values that would provide the highest concordance with the IHC status of the target protein. On the contrary, we regarded IHC ER and PgR protein expression determination as the most widely used analytical assay, but not the gold standard, in view of its moderate predictive value for benefit from endocrine therapies, semiquantitative nature of results and inter-or intra-laboratory reporting variability [2,3,[8][9][10]. Using distributional studies of mRNA values and taking into account hormonal receptor protein staining as a gross template, we sought to study the predictive value and correlation of a more conservative threshold, the 25th percentile of mRNA values, in order not to miss an effect of low, but potentially biologically significant level of messenger RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most studies the investigators actually intended to identify those kRT-PCR mRNA cutoff values that would provide the highest concordance with the IHC status of the target protein. On the contrary, we regarded IHC ER and PgR protein expression determination as the most widely used analytical assay, but not the gold standard, in view of its moderate predictive value for benefit from endocrine therapies, semiquantitative nature of results and inter-or intra-laboratory reporting variability [2,3,[8][9][10]. Using distributional studies of mRNA values and taking into account hormonal receptor protein staining as a gross template, we sought to study the predictive value and correlation of a more conservative threshold, the 25th percentile of mRNA values, in order not to miss an effect of low, but potentially biologically significant level of messenger RNA.…”
Section: Discussionmentioning
confidence: 99%
“…These women become disease-free following surgical resection of the tumor and may be candidates for adjuvant systemic therapy aiming at eradication of micrometastatic deposits [1]. Estrogen receptor (ER) protein expression, studied by means of immunohistochemical (IHC) staining, is the gold standard for the selection of patients who will be managed with hormonal therapy, though its predictive value for benefit from such treatment is modest (30-60%) [2,3]. Several clinicopathological parameters, including tumor size, grade, ER status, axillary nodal status, patient age, and Human Epidermal growth factor Receptor-type 2 (HER2) overexpression are taken into consideration in order to identify which patients are most likely to benefit from administration of adjuvant cytotoxic chemotherapy and which drugs should be used [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…), compared them against placebo or other SSRIs, and evaluated vasomotor symptoms (daily hot flash frequency or improvement in vasomotor scores). We specifically excluded studies that enrolled cancer patients and patients receiving selective estrogen receptor modulators (SERMs) because hot flashes and night sweats are common complaints (up to 80 %) of patients receiving tamoxifen for breast cancer, [14][15][16] women taking hormonal replacement therapy and patients with diagnoses of depression.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Two randomized, double-blind studies demonstrated that anastrozole (1 mg daily) was slightly more effective than tamoxifen (20 mg daily) as first-line therapy in postmenopausal women with advanced breast cancer. Among those with ER+ tumors [84][85][86], the benefit was significant in terms of partial and complete responses including stable disease as well as time to progression. In a multicenter, randomized, double-blind study in advanced breast cancer, letrozole proved to be significantly better than tamoxifen in response rate, clinical benefit, time to progression, and time to treatment failure [87].…”
Section: The Road To Adjuvant Treatment With Aromatase Inhibitorsmentioning
confidence: 99%